2021
DOI: 10.1038/s41467-021-24804-3
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate-functionalized patch confers cardioprotection and improves heart repair after myocardial infarction via local nitric oxide delivery

Abstract: Nitric oxide (NO) is a short-lived signaling molecule that plays a pivotal role in cardiovascular system. Organic nitrates represent a class of NO-donating drugs for treating coronary artery diseases, acting through the vasodilation of systemic vasculature that often leads to adverse effects. Herein, we design a nitrate-functionalized patch, wherein the nitrate pharmacological functional groups are covalently bound to biodegradable polymers, thus transforming small-molecule drugs into therapeutic biomaterials.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 69 publications
2
59
0
Order By: Relevance
“…Patching up the tissues represented a sustained delivery manner for therapeutics 47 . In this study, we fabricated a fully acellular ORP by embeding synMSC particles in a widely used SPS.…”
Section: Discussionmentioning
confidence: 99%
“…Patching up the tissues represented a sustained delivery manner for therapeutics 47 . In this study, we fabricated a fully acellular ORP by embeding synMSC particles in a widely used SPS.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, PCL ( M n 80,000) was mixed with PCL-ONO 2 ( M n 2,000) at blending ratios of 9/1 (w/w), according to our previously published protocol ( Zhu et al, 2021 ). The mixture was dissolved in mixed chloroform/methanol (5:1, v/v) by sufficient stirring to obtain homogeneous solution with a final concentration of 10% (w/v).…”
Section: Methodsmentioning
confidence: 99%
“…NO is essential in maintaining cardiovascular homeostasis ( Yang et al, 2018 ) and dysfunctions in NO signaling is often an associated-complication of CVD pathologies ( Erdmann et al, 2013 ). NO-based interventions were shown to attenuate myocardial infarction ( Rassaf et al, 2014 ; Zhu et al, 2021 ), thrombus formation ( Heusch, 2015 ; Heusch and Gersh, 2017 ; Yang et al, 2020a ), and convey immunomodulatory and cardioprotective effects ( Bogdan, 2001 ; Chouchani et al, 2013 ). NO release or generation mechanisms have been incorporated into multiple cardiovascular implants, including stents ( Zhang et al, 2019 ; Yang et al, 2020b ) and vascular grafts ( Wang et al, 2015 ), with demonstratable benefits to the promotion of angiogenesis, re-endothelialization, and vascular tissue regeneration ( Yang et al, 2015 ; Li et al, 2018 ; Kabirian et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a very recent investigation, another research group produced a scaffold coupled with nitric oxide (NO), another cardioprotective agent [ 99 ]. Exogenous NO delivery exhibits its cardioprotective effect against MI injury, acting on CMs survival and improving their contractility.…”
Section: Functionalised Acellular Scaffoldsmentioning
confidence: 99%
“…Further, the therapeutic potential of these patches was translated into a large animal model of acute MI where they demonstrated suppressed adverse LV remodelling. Interestingly, besides enhanced cardiac function and decreased infarct size, this study reported a significant increase in CMs proliferation at the border zone of the infarct size accompanied by enhanced capillary and arteriolar density [ 99 ].…”
Section: Functionalised Acellular Scaffoldsmentioning
confidence: 99%